Pengaruh Media Pembelajaran Aplikasi Assemblr Edu Terhadap Pemahaman Siswa Pada Materi Siklus Air - Zarvin Ridho Subhan; Sukardi Sukardi; Aldora Pratama (Journal on Education, 2023)
This study aims to determine whether there is any influence of the Assemblr Edu application learning media on students' understanding of the water cycle material for class V SD Negeri 7 Air Kumbang. The population is class V totaling 53 students. by using a sample of 53 students who were randomly selected, namely class V.A and class V.B. The method in this research is quantitative experiment design true Experiment Design with the Posttest Only Control Group Design test. Testing the hypothesis using the Independent Sample T-test t-test. After carrying out the post-test on the water cycle material, the experimental class obtained an average value of 76.48 and the control class obtained an average value of 69.80. Through the Independent Sample T-Test t-test, the results are t_count 2.790 > t_table 2.008. So it can be concluded that there is an influence of the Assemblr Edu application learning media on students' understanding of the water cycle material.